Timing and the control of rhythmic upper-limb movements - Shafir, T.; Brown, S. H. (Journal of Motor Behavior, 2010)
Accurate timing of limb displacement is crucial for effective motor control. The authors examined the effects of movement velocity, duration, direction, added mass, and auditory cueing on timing, spatial, and trajectory variability of single- and multijoint rhythmic movements. During single-joint movements, increased velocity decreased timing and spatial variability, whereas increased movement duration increased timing variability but decreased spatial variability. For multijoint movements, regardless of condition, increasing velocity decreased joint timing, spatial, and trajectory variability, but all hand variabilities were unaffected by velocity, duration, load, or direction. Timing, spatial, and trajectory variability was greater at the shoulder compared with the elbow and minimal at the hand, supporting the notion that reaching movements are planned in hand space as opposed to joint space.